PERAN GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MENGATASI KENAKALAN PESERTA DIDIK - Aryanti Dwi Untari; Nurfitriana Nurfitriana (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This study aims to find out how the role of pancasila and citizenship education teachers in addressing the delinquency of learners in MTs Al-Khairiyah Kepandean, what are the forms of delinquency of learners in MTs Al-Khairiyah Kepandean and what are the obstacles of teachers pancasila education and citizenship in overcoming mischief students in MTs Al-Khairiyah Kepandean. This research uses qualitative research method, with descriptive approach. Data collection conducted by using interview techniques, observation, and documentation later processed again and examined by using triangulation techniques that aim to check the validity of data. The results of this study illustrate that the role of Pancasila and citizenship education teachers in addressing the delinquency of learners in MTs Al-Khairiyah Kepandean done through the role as a mentor, role as a moral agent, role as communicator and role as model. The forms of delinquency of learners in MTs Al-Khairiyah Kepandean are included in a-social and a-moral delinquency and can be categorized into mild mischief. The barriers of Pancasila and citizenship education teachers in dealing with delinquency of students in MTs Al-Khairiyah Kepandean are derived from family factors, environmental factors and schools.